Helping Children Victims Of Sexual Violence By The Center For Integrated Services For Women And Children Empowerment (P2TP2A) Maros Regency - Andi Megadara Santri Ramadhana (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2021)
Violence is an act that causes misery or suffering physically, psychologically, sexually or acts who neglects someone to do any acts of force, any coercion, or unlawful deprivation of liberty. This act of violence is a crime that often occurs in Indonesia, including sexual violence. Sexual violence in which the majority of the victims are women and children. however, they're often on the highlight of the news that is displayed on newspaper or e-news. Children was a gift from God and they're the next generation of the nation's ideals who should be receive special protection as stipulated in the positive law of Indonesia. The impact of sexual violence is very detrimental to children both for their physically and psychologically.